Menempuh Ujian Biomedis : Persiapan dan Cara-Caranya - T. Jacob, T. Jacob (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1980)
This article discusses the aims and various kinds of biomedical examinations and their evalua Ã¢â¬Â¢ Lion, primarily to assist those preparing for such undertakings. Among those aims, examination as a measure for protection of the public against incompetence and for quality control seems to be gradually disemphasized.Practical hints and "pearls" are given for passing various examinations, ranging from quizzes and pre-practical tests to subspecialty and doctorate examinations, and from viva voce and objective examinations to clinical and thesis examinations. Candidates are advised to know beforehand the system of evaluation and grading used in their examinations which could vary from pass/fail to 0-100 scale marking, and from continuous, comprehensive assessment to grading on the class curve. The discussion dwells on special techniques and procedures, such as rapid reading, analytical reasoning. the diagnostic process, and "post-mortem" evaluation of ones performance.Key Words: biomedical examination - viva voce - clinical examination - problem solving -diagnostic process